Characterization of Malaysian sweet potato ‘Anggun 1’ variety at different storage temperatures and processing conditions - Shaari, Nurfarhana (2021)
After harvest, the quality of sweet potato is reduced due to loss of physical appearances and biochemical properties. In order to maintain sweet potato quality during storage, sweet potato (Anggun 1) needs to be stored at suitable postharvest storage condition. Thus, the first objective was undertaken to determine the potential postharvest storage condition that would extend the physical and chemical, phytochemical and mechanical properties of Anggun 1. A total 350 samples of Anggun 1 were obtained and stored at two different storage temperatures (10⁰C and 27⁰C) for a period of 6 weeks. After every 1 week of storage, respective samples were taken out and were measured the physical and chemical (moisture, dry matter, weight loss, shrinkage, dry matter, carbohydrate and starch), phytochemical (total phenolic, total flavonoid and anthocyanin content) and mechanical (penetration and compression test) properties. Results revealed that storage at 10⁰C could preserve more physical and chemical properties of Anggun 1 than at 27⁰C. The slower degradations of phytochemical properties were observed during storage at 10⁰C. Storage at 10⁰C also could better retain the mechanical properties of Anggun 1 than at 27⁰C. Therefore, the most suitable storage condition for Anggun 1 is at 10⁰C because at this condition the physical and chemical, phytochemical and mechanical properties were more stable than at 27⁰C for 6 weeks storage. An understanding of kinetic modeling is important to the food industry in order to minimize losses of quality in food products during storage. It can be achieved through the development of mathematical models to predict the behavior of food quality changes. Therefore, the second objective was to determine the kinetic models (zero, first and second-order) that describe the quality changes in Anggun 1 during 6 weeks of storage. All the data from the first experiment were fitted with zero, first and second-order models using nonlinear regression performed by statistical method. The selection of the best fitted model was confirmed by the determination coefficient (R2). Result revealed that the changes of quality attributes of Anggun 1 during storage can be described using zero and first-order model. In this objective, the shelf life of Anggun 1 also predicted based on weight loss analysis. The result showed that Anggun 1 retained higher shelf life at 10⁰C than at 27⁰C. This indicated that storage at 10⁰C is more effective storage method for slowing down the damage of Anggun 1’s quality attributes. The processing of sweet potato into end products involves peeling which causes nutritional loss and influences the chemical composition. However, peeling had an advantage in giving better processing characteristic of sweet potato products. Thus, the third objective was done to select the best condition of Anggun 1 through differentiation characteristics of unpeeled tuber (C1), peeled tuber (C2) and skin of tuber (C3) on the physical and chemical, phytochemical properties, mineral and anti-nutrient composition. Anggun 1 was characterized into three different conditions (C1, C2 and C3) in terms of tuber and flour. Result showed that peeling caused significant loss of physical and chemical (moisture content, dry matter, fiber, carbohydrate and amylose), phytochemical (total phenolic content and carotenoid), mineral (calcium) and anti-nutrient (phytate, tannin and trypsin inhibitor activity) in Anggun 1’s tuber and flour. It is concluded that the peeling process was responsible for causing the loss of physical and chemical, phytochemical, mineral and anti-nutrient composition of Anggun 1. It also can be observed that C1 for tuber and flour of Anggun 1 had higher dry matter, carbohydrate, amylose, total phenolic, carotenoid, phytate, tannin and trypsin inhibitor activity than other conditions. Therefore, it is suggested that C1 of Anggun 1’s tuber and flour is the best condition in improving the quality of sweet potato because it has been proven to reduce the loss of physical and chemical, phytochemical properties, mineral and anti-nutrient composition.